The Migration Effect on an Eco-toxicant Model - Majeed, Azhar Abbas (Iraqi Journal of Science, 2024)
This paper proposes and studies an ecotoxicant system with Lotka-Volterra functional response for predation including prey protective region. The equilibrium points and the stability of this model have been investigated analytically both locally and globally. Finally, numerical simulations and graphical representations have been utilized to support our analytical findings.